Morphology and fracture porperties relationship of epoxy-diamine systems simultaneously modified with polysulfone and poly(ether imide) - Giannotti, Marina Inés (2005)
An epoxy-diamine system was simultaneously modified with two immiscible thermoplastic polymers, polysulfone (PSF) and poly (ether imide) (PEI), to develop tough materials without adding high quantities of modifiers, in order to avoid the processibility problems caused by the high initial viscosity of the mixtures. The mechanical behavior of blends containing 10 and 15 wt% total thermoplastic was analyzed and compared with the generated morphologies. The scanning electron micrographs (SEM) of the broken surfaces showed that when a small part of PEI is replaced by PSF, drastic changes in morphology, leading to co-continuity between the phases, occurred together with fracture (critical stress intensity factor, KIC) improvements. As an additional advantage, no noticeable decrease in the elastic modulus (E) of final materials was observed.